Circular dichroism spectroscopy analysis of conformational transitions of a 54 base pair DNA duplex composed of alternating CGCGCG and TATATA blocks - Kypr, J; Stepán, J; Chládková, J; Vorlícková, M (Biospectroscopy, 1999)
CD spectroscopy was used to analyze conformational properties of a self-complementary 54-mer DNA composed of alternating (CG)3 and (TA)3 hexamers. NaCl induced the Z-form in poly(GC), but the 54-mer remained the B-form under the same conditions. The B-Z transition was induced only after the addition of NiCl2. However, the Z-form was adopted by the whole molecule, not by the (CG)3 blocks alone. Two orders of magnitude higher concentrations of NiCl2 were required to induce the Z-form in poly(AT). The Z-form was also induced in poly(GC) by CsF that switched poly(AT) into the X-form, which seems to be a solution counterpart of D-DNA. Under these conditions the CD spectrum of the 54-mer was consistent with the (TA)3 blocks being in the X-form and the (CG)3 blocks in the B-form. At high concentrations of ethanol or trifluoroethanol, poly(AT) was an A-form, while poly(GC) adopted either Z-form, A-form or Z'-form. At the high trifluoroethanol concentrations the 54-mer cooperatively switched into a conformation whose CD spectrum was most consistent with the A-form in the (TA)3 blocks and the Z'-form in the (CG)3 blocks. This suggests that the base pairs are tilted in the Z'-form as in the A-form. The present article illustrates that CD spectroscopy can provide interesting pieces of information about conformational isomerizations and coexistence of multiple conformations in DNA molecules containing blocks of different simple sequence repeats.
Keywords: Circular Dichroism; cirkulární dichroismus; Base Pairing; heteroduplexy nukleové kyseliny; párování bází; Nucleic Acid Conformation; rozpouštědla; Nucleic Acid Heteroduplexes; sekvence nukleotidů; Base Sequence; Solvents; Trifluoroethanol; trifluorethanol; konformace nukleové kyseliny